A Biotechnology Course for Developing Countries - Karim M Maredia; Joseph F. Guenthner; Cholani K. Weebadde (Journal of International Agricultural and Extension Education, 2012)
Biotechnology offers benefits, but few developing countries have approved genetically engineered (GE) crops. Extension educational programs could help prepare stakeholders in developing countries to influence biotechnology policies. Michigan State University (MSU) developed a two-week course that was taught 14 times from 2002 to 2010 for 251 participants from 58 developing countries. This course helped form an international network of biotechnology specialists who collaborate with stakeholders.
Keywords: Agricultural Biotechnology; Biosafety; Capacity Building; Developing Countries; Education; Training; Transgenic Crops